The Impact of Entrepreneurial Optimism and Labor Law on Business Performance of New Ventures - Li, Shuai; Wu, Dongshuo; Sun, Youxia (Frontiers in Psychology, 2021)
The purpose is to study the internal relationship between entrepreneurial optimism and business performance of new ventures, and the impact of entrepreneurial optimism on the business performance of new ventures. Based on the literature review, the hypotheses that entrepreneurial optimism has a positive impact on the business performance of new ventures, and that labor law plays a mediating role in the impact are put forward. Then the questionnaire is designed according to the maturity scale, and 200 questionnaires are collected. Finally, the descriptive statistical analysis, reliability analysis, exploratory factor analysis, confirmatory factor analysis, correlation analysis, and regression analysis of the theoretical model and hypothesis are carried out by using the statistical analysis software spsss22.0. The results show that each dimension of entrepreneurial optimism has a significant positive impact on the business performance of new ventures, and labor law plays a mediating role between them. This study provides a new idea for the establishment of the performance impact mechanism of new ventures and helps new entrepreneurs realize the importance of maintaining an optimistic attitude, improving the business performance of new ventures.